Analysis and testing of a superconducting maglev submersible cryogenic liquid pump. Issue 4 (15th February 2022) - Ai, Liwang; Zhang, Guomin; Xu, Xiaozhuo; Feng, Haichao; Cao, Wenping
Abstract: This paper studies a superconducting maglev submersible cryogenic liquid pump (CLP) using superconducting magnetic bearing (SMB). A new structure is proposed for the self‐stability of high‐temperature superconducting magnetic levitation, and the compact structure of disk motor‐pump. The rotor of the axial‐flux disk motor is connected with a centrifugal impeller to form an impeller‐rotor of the proposed superconducting CLP. Supported by a SMB system, the impeller‐rotor rotates frictionlessly with self‐stabilisation as a suspension rotor. The SMB system includes a radial‐type SMB, an auxiliary permanent magnet bearing, and an electromagnetic bearing composed of the stator and the rotor of disk motor. Theoretical calculations and experimental measurements are performed to examine the axial and radial levitation force behaviours of the SMB system. Then, a kinetic model of the suspension rotor is established and analysed to assure force balance and stable levitation. Finally, a prototype pump is fabricated and an experimental setup for liquid nitrogen transmission is constructed for validation purposes. The experimental tests on the pump head and the flow rate are carried out, which demonstrate the effectiveness of the proposed superconducting maglev submersible CLP.